2016
DOI: 10.1007/s10067-016-3433-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of neopterin is not a marker of disease activity in treated rheumatoid arthritis patients

Abstract: Neopterin has been measured in many autoimmune diseases and was reported as a marker of cellular immunity activation in rheumatoid asthritis (RA). The aim of this work was to assess serum neopterin as a marker of disease activity in treated RA patients. We measured serum level of neopterin in 120 treated RA patients and 100 age- and sex-matched controls by high-performance liquid chromatography (HPLC) method, and disease activity score was calculated in all patients by DAS28-CRP score. Significantly higher lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
3
18
1
Order By: Relevance
“…However, in contrast to our study, El-Lebedy et al (15) found no significant correlations between neopterin levels and any of the disease activity parameters.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, in contrast to our study, El-Lebedy et al (15) found no significant correlations between neopterin levels and any of the disease activity parameters.…”
Section: Discussioncontrasting
confidence: 99%
“…D'agostino et al (13) also agreed with our study results as the mean neopterin concentrations in early JIA patients (8.92nmol/l)were significantly higher than the mean neopterin concentrations in healthy volunteers (5.62 nmol/l). This is also in agreement to El-Lebedy et al (15) who found significantly higher levels of neopterin in JIA patients (11.46 ± 3.56 nmol/L) compared to healthy controls (4.74 ± 1.98 nmol/L).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Neopterin indicates a proinflammatory condition and increased status of oxidative stress. The most important trigger of neopterin is interferon‐γ, which is secreted from activated T‐helper cells . In recent studies it was shown that high neopterin levels are related to cardiovascular diseases, stroke and autoimmune diseases like rheumatoid arthritis, several infections, diabetes mellitus and malignancies …”
Section: Introductionmentioning
confidence: 99%
“…The most important trigger of neopterin is interferon-γ, which is secreted from activated T-helper cells. 6,7 In recent studies it was shown that high neopterin levels are related to cardiovascular diseases, stroke and autoimmune diseases like rheumatoid arthritis, several infections, diabetes mellitus and malignancies. [8][9][10][11] Ischemia and increased oxidative stress bring structural changes which affect the N-terminal peptides of albumin.…”
Section: Introductionmentioning
confidence: 99%